Business process management and innovation dynamics in a South African Bank - Chang, Kai-Ruin (University of the Witwatersrand, Johannesburg, 2023)
Innovation has been a topical focus for banks in achieving strategic value through new products development, efficient processes and improved services. Whilstdriving innovation, banks are however faced with barriers such as inertia exerted by legacy systems, unsupportive organisation structures and restrictive mindsets that are too risk avoidant. Thus, how innovation is managed by banks has become critical in overcoming these barriers. Despite business process management (BPM) having an overlapping objective to that of innovation management in achieving efficiency and lowering costs for an organisation, it has developed as a separate discipline to that of innovation management. The purpose of this study is the exploration of integrating BPM principles in innovation management in banks to overcome barriers and provide practical recommendations. The study further aims to contribute to the gap that exists between the body of academic knowledge and what innovation managers are aware of in a South Africa bank context. In this study, data were collected through semi-structured interviews with senior employees within a South African bank. The data were further analysed using a qualitative research method to identify and interpret themes based on interviews with subject matter experts and managers in the South African bank. The study has identified the key layers from the total innovation management paradigm and BPM principles that can enable the innovation performance for a bank and raises further areas that can be explored
A research report submitted to the Faculty of Commerce, Law and Management, University of the Witwatersrand, in partial fulfillment of the requirements for the degree of Master of Management in Innovation Studies Johannesburg, 2023
Keywords: Innovation; Banking; Business process management (BPM); South African ban; UCTD; SDG-8: Decent work and economic growth